Outcome of mock embryo transfer before the first IVF cycle: A randomized control trial - Amol Borkar; Amit Shah; Anil Gudi; Roy Homburg (Shahid Sadoughi University of Medical Sciences, 2020)
Background: There is a lack of agreement among fertility specialists with regard to the routine use of mock embryo transfer (MET) before each in vitro fertilization (IVF) treatment cycle. While MET may be beneficial with previous difficult embryo transfer cases, its routine use before first IVF cycle has not been evaluated. Objective: To find out the effect of MET before the first IVF cycle on clinical pregnancy rate. Materials and Methods: This is a single-centre randomized controlled trial with a balanced randomization (1:1), carried out between November 2015 and October 2017, with 200 subjects at Homerton university hospital, London, randomized into either MET or control. The primary outcome was clinical pregnancy rate (detection of heart activity on the ultrasound scan), the secondary outcome measures were live birth rate, miscarriage and multiple pregnancy rates, difficult ETs, rate of blood or mucus on the catheter tip. Results: No significant differences were observed in the baseline or cycle characteristics between the two groups. The clinical pregnancy rate was similar between the MET and control groups based on both intension to treat and per protocol analyses (p = 0.98, p = 0.92, respectively). Additionally, no significant difference was seen in the live birth rate in both groups on intension to treat and per protocol analyses (p = 0.67, p = 0.47), respectively. Conclusion: Our study concludes that MET prior to first IVF cycle may not improve the success rate in young women without risk factors for a difficult embryo transfer.